Murabahah: A Strategic Solution For Credit Risk Mitigation In Islamic Banking - Qizwini, Jimmi; Huda, Nurul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Murabahah, a Sharia-compliant financing instrument, is recognized as an essential tool for mitigating credit risks in Islamic banking, offering a transparent and asset-backed approach to financial transactions. Islamic banks, operating within the prohibition of interest-based systems, face significant challenges in managing credit risks while ensuring adherence to ethical and religious principles. This study explores the role of Murabahah in reducing credit risks by emphasizing its structured payment mechanisms, risk-sharing attributes, and collateral-backed nature, which collectively lower default risks and enhance transaction transparency. The novelty of this research lies in its focus on Murabahah’s specific function in credit risk mitigation, an area often underexplored in existing literature. Utilizing a qualitative descriptive approach, the research analyzes how Murabahah fosters financial stability by tying financing to tangible assets, thereby minimizing uncertainty and moral hazard. The findings indicate that Murabahah effectively aligns risk management strategies with Sharia principles, offering a sustainable solution for Islamic banks to navigate financial challenges without compromising their ethical values. However, the study also identifies potential limitations, including the over-reliance on Murabahah and market-specific constraints. This research contributes to the understanding of Islamic finance by highlighting Murabahah’s critical role in balancing financial stability and ethical compliance, providing practical insights for improving the risk management frameworks of Islamic financial institutions.